Effect of carbon fiber‐graphene oxide multiscale reinforcements on the thermo‐mechanical properties of polyurethane elastomer. (6th February 2018) - Jiang, Shuai; He, Zhenglong; Li, Qifeng; Wang, Junwei; Wu, Gangping; Zhao, Yuhua; Kang, Maoqing
Abstract : Thermo‐mechanical properties are often the bottleneck for advanced applications of polyurethane (PU) elastomer materials. Carbon materials are emerging as promising reinforcing fillers for polymers due to their superior mechanical and conductive properties. In this study, carbon fiber‐graphene oxide (CF‐GO) multiscale reinforcements are fabricated for improving thermal‐mechanical properties of PU elastomers. To this end, CFs are firstly modified with GO via electrophoretic deposition and subsequently cooperate with free‐dispersed GO sheets in PU matrix. This multiscale reinforcing strategy effectively improved thermo‐mechanical properties and thermal stability of PU elastomer due to the improved CF‐PU interfacial interaction as well as the local stiffening of fiber‐matrix interphase by the dispersed GO sheets. This reinforcing approach also led to a synergistic increase in the thermal diffusivity of PU elastomer due to the formation of interconnected conductive network, in which CFs serve as a conductive framework that connects the free‐dispersed GO sheets. POLYM. COMPOS., 40:E953–E961, 2019. © 2018 Society of Plastics Engineers